Smart Contracts to Support the Advancement of Blockchain Technology in the Security Integrity - Sulistiawati wati (IAIC Publishing, 2020)
The development of technology today is used as a benchmark in the advancement of the industrial world where the development of technology has influenced various aspects in the life of today's society. Smart contracts as one form of blockchain technology that resembles a conventional contract can be used to bind agreements between one party and another. One difference between a smart contract and a conventional contract is the smart contract that is stored in the blockchain. With the presence of smart contracts on the blockchain has become one of the most sought-after technologies, because the number of users is high enough for each transaction within the company. In this case various features of smart contracts applications in various worlds, ranging from financial services, life sciences, energy resources and media voting. Smart contracts still pose a lot of challenges that overwhelm the interaction of some Parties, such as users, developers, and organizations built on smart contracts. Smart contracts are essentially a very effective source of problem solvers, where smart contracts on the blockchain make it easy to maintain data security, and save costs and time. In addition, in the absence of third parties strongly minimizes the fraud that is often done by irresponsible parties, this prevents conflicts between parties. Prone to cases of loss of a document is generated because there is no secure storage media. The advent of smart contracts on the blockchain is expected to be a solution to tackle most of the world's commercial and bureaucratic systems.